Antigen presentation events during the initiation of autoimmune diabetes in the NOD mouse. (July 2016) - Ferris, Stephen T.; Carrero, Javier A.; Unanue, Emil R.
Abstract: This is a brief summary of our studies of NOD autoimmune diabetes examining the events during the initial stage of the process. Our focus has been on antigen presentation events and the antigen presenting cells (APC) inside islets. Islets of non-diabetic mice contain resident macrophages that are developmentally distinct from those in the inter-acinar stroma. The autoimmune process starts with the entrance of CD4+ T cells together with a burst of a subset of dendritic cells (DC) bearing CD103. The CD103+ DC develop under the influence of the Batf3 transcription factor. Batf3 deficient mice do not develop diabetes and their islets are uninfiltrated throughout life. Thus, the CD103+ DC are necessary for the progression of autoimmune diabetes. The major CD4+ T cell response in NOD are the T cells directed to insulin. In particular, the non-conventional 12–20 segment of the insulin B chain is presented by the class II MHC molecule I-A g7 and elicits pathogenic CD4+ T cells. We discuss that the diabetic process requires the CD103+ DC, the CD4+ T cells to insulin peptides, and NOD specific I-Ag 7 MHC-II allele. Finally, our initial studies indicate that beta cells transfer insulin containing vesicles to the local APC in a contact-dependent reaction. Live images of beta cells interactions with the APC and electron micrographs of islet APCs also show the transfer of granules.